Trauma of bone and soft tissues in South American mummies—New cases provide further insight into violence and lethal outcome - Begerock, Anna-Maria; Loynes, Robert; Peschel, Oliver K.; Verano, John; Bianucci, Raffaella; Martinez Armijo, Isabel; González, Mercedes; Nerlich, Andreas G. (Frontiers in Medicine, 2022)
There exist numerous reports on violence in South American populations which shed a particular light on life and living conditions in those historic communities. Most studies have been performed on collections of isolated skulls. Whole-body investigations especially on well-preserved mummified human remains are rare. In the present study we investigated three South American mummies predating the Colonial Spanish period. The “Marburg” man lived between 996 and 1147 CE and was buried in typical burial bundle. The analysis of the textiles, ceramics and fishing tools associated with his naturally mummified body suggests that he most likely originated from the Arica region in Northern Chile and was possibly part of a fishing community. The “Delémont” natural mummies belong to an adult male and an adult female, respectively. The mummies, the textiles and grave goods were investigated. The ceramics suggest a provenance from the Arequipa region, supposing that all the artifacts were originally associated with the two mummies. The Delémont male mummy is 14C dated between 902 and 994 CE and the “Delémont” female mummy 14C dated between 1224 and 1282 CE. All mummies underwent Multidetector Computed Tomography which showed evidence of trauma, some of which were interpreted as evidence of interpersonal violence. An interdisciplinary approach was applied with the particular intention to identify trauma sequels and to evaluate their paleo-forensic potential. Evidence of violence was identified in the two male individuals. Our study provides evidence that the interdisciplinary investigation of well-preserved human remains may detect much more frequent traces of intentional trauma than previously thought. Particularly, trauma against the body may not be identified in studies on skulls alone, and trauma residues of internal organs/soft tissues will only be seen in mummies. We therefore add further evidence of two cases of (lethal) trauma in pre-colonial South-American male individuals.